PENGARUH PENDIDIKAN KESEHATAN MEDIA E-BOOKLET TENTANG PERTOLONGAN PERTAMA CEDERA OLAHRAGA TERHADAP TINGKATPENGETAHUAN REMAJA - Ari Wiryansyah, Oscar; Nur Janah, Risti (LPPM STIKes Mitra Adiguna, 2025)
Sports injuries are pain caused by sports that can lead to disability, injury or damage to muscles, joints and other parts of the body. If sports injuries are not treated quickly and properly, they can also lead to difficulties in performing various daily activities or the sport in question. With the existence of this Media Health Education E-Booklet, it is important for students to prevent aggravation when they suffer a sports injury. The purpose of this study was to determine “The Impact of the Media Health Education E-Booklet on First Aid for Sports Injuries on Adolescents' Knowledge Level”. This research method is quantitative. This study uses a pre-experimental design with a one-group before and after test design. The population used in this study was all students of SMK Telenika Palembang, a total of 51 respondents who met the inclusion and exclusion criteria. The instrument used in the study was a questionnaire. The data analysis used was univariate and bivariate. The results showed that the average knowledge of adolescents increased by about 25.05% before and after health education. Based on the statistical analysis, this change has a p-value of 0.000, indicating a significant change. Therefore, e-booklets have been proven to be effective in increasing adolescents' knowledge of first aid for sports injuries.